2019
DOI: 10.2478/nor-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

Logic of an Effectuating Hyperlocal

Abstract: This article examines motivations, rewards and strategies in hyperlocal news entrepreneurship. The material is an interview study with eight entrepreneurs who independently own and manage hyperlocal news sites in Sweden. The conclusion is that the means of the hyperlocal entrepreneur both motivate and create an obstacle for growth. The findings of struggling business models, self-exploitation and civic motivations correspond with previous research in different countries, but alternative perspectives are sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…The scholarly discussion links this development of experimentation with new technologies and challenging of boundaries for what is considered journalism to the downsizing of the media industry. In this context, downsizing has had a positive effect by encouraging journalists to start their own businesses and propose their own journalistic innovations (Cohen, 2015;Raviola, 2019;Tenor, 2019). Cook and Sirkkunen (2015) divided digital native start-up sites into two categories: storytelling and service-orientation.…”
Section: The Rise and Success Of Digital News Start-upsmentioning
confidence: 99%
“…The scholarly discussion links this development of experimentation with new technologies and challenging of boundaries for what is considered journalism to the downsizing of the media industry. In this context, downsizing has had a positive effect by encouraging journalists to start their own businesses and propose their own journalistic innovations (Cohen, 2015;Raviola, 2019;Tenor, 2019). Cook and Sirkkunen (2015) divided digital native start-up sites into two categories: storytelling and service-orientation.…”
Section: The Rise and Success Of Digital News Start-upsmentioning
confidence: 99%
“…Este fenómeno, observado a nivel internacional, se vio favorecido por el bajo coste para la producción y distribución de contenido en la red, la creciente demanda de información local o el cambio de comportamiento de las audiencias hacia roles más activos (Radcliffe, 2015). Este tipo de proyectos buscan, por lo común, ocupar el hueco informativo olvidado por los grandes medios tradicionales, ofrecer una alternativa que visibilice el área geográfica local e hiperlocal y dé voz a sus vecinos, así como desarrollar una función social Tenor, 2019).…”
Section: Introductionunclassified
“…For example, studies have found factors that can influence the company's internationalization (Bai, Johanson, Oliveira, Ratajczak-Mrozek, & Francioni, 2022;Crick & Crick, 2015Kalinic et al, 2014). On the one hand, some factors influence the business model, interrelationships, and intracompany (Crick & Crick, 2018;Fiedler, Fath, & Whittaker, 2017;George, Kotha, Parikh, Alnuaimi, & Bahaj, 2016;Tenor, 2019;Tokunaga, Martinez, & Crusat, 2018;van Bommel et al, 2014). On the other hand, there are factors related to teams and managing internal companies (Crick, Crick, & Chaudhry, 2020;Hunt et al, 2021;Renton & Simmonds, 2019).…”
Section: Performancementioning
confidence: 99%